Perception of the usefulness of dental records as a method of human identification in high-risk professions: the case of the Costa Rican Red Cross workers - Fernández Chaves, José Manuel (2023)
Introduction: Those who provide care in emergency situations are exposed to a high risk of injury or death during rescue work, whether in traffic accidents, natural disasters, terrorist attacks, or humanitarian crises generated by armed conflicts. This research was carried out among Costa Rican Red Cross (CRC) workers to establish the perception of the usefulness of dental records as a method of identification and to develop a single format for antemortem dental information. Materials and methods: A pilot questionnaire was designed and applied to 10 persons to be calibrated and validated. Subsequently, a final electronic questionnaire was generated in the Google Forms platform and sent via institutional e-mail to 175 workers, of whom 92 responded during the period from November 20, 2022, to January 20, 2023. The results were analyzed by means of frequency distributions, crossing of variables, and comparison of means based on the analysis of variance. The minimum confidence level for comparisons was 95%. Results: The questionnaire was completed by 92 people, 75% men and 25% women. The age range between 36 and 40 years was the most frequent (23.9%). A total of 60.9% worked in the province of San José, 58% indicated that they had visited the dentist a year ago or less and 38.6% said that they had never had a panoramic X-ray taken, 81.8% said they had dental treatments such as crowns, bridges or implants; and 75% considered dental records to be very useful as a method of identification, and placed it in second place in terms of knowledge (89.8%) when compared with DNA (97.7%) and dactyloscopy (86.4%). Conclusions: Costa Rican Red Cross workers consider dental records to be useful in the identification of human beings and have useful antemortem information for this purpose.